Effects of Visual Approach in Teaching Mathematics for Malaysian Secondary School: A Case Study - Zulmaryan Embong; Nor Syamimi Mohamed Adnan; Nurhafizah Saidin; Hasniza Ibrahim, (Journal of Human Development and Communication (JoHDeC), 2025)
Previous studies have shown that students have difficulties when dealing with abstract and lengthy questions. Therefore, the main purpose of this study is to investigate the significant difference in students’ performance when using visual approach in teaching and learning mathematics. The population used for this study was students in secondary form two from one of the selected schools in Gombak district. Eighty-five students were selected as respondents for this study. The pre-post design and questionnaire techniques were adapted from previous literature in this study. Firstly, a pre-test was given to all the respondents. Then, the respondents were facilitated with the treatment by using the visual approach. Subsequently, a post-test was administrated. Lastly, a set of questionnaires was distributed to the students in order to get the students’ feedback. The raw scores from the pre-test and post-test were analysed by using Sample-Paired T-test. Meanwhile, the descriptive statistic was used to analyse the data from the questionnaires. The results reveal that the visual approach can increase the students’ performance in mathematics. Thus, the study strongly recommends further study to be conducted by increasing the number of samples so that the generalization can be made to another school as well. It is also recommended that the study should take the students’ backgrounds into consideration such as gender, ethnicity and cultures.